Audience Reception to the Creativity and Humor Elements in the Sasa Advertisement “Persembahan Terbaik dari Sasa Omega 3” - Wiqoyati, Arum; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2024)
Humor is a familiar aspect of everyday life and plays a significant role in Indonesian society. This is evident in various contexts and forms of everyday communication, media, entertainment, and advertisements. The creativity and humor in Indonesian advertisements reflect diverse and unique approaches to creating campaigns that capture the audience’s attention. This research aims to understand and describe how audiences perceive the elements of creativity and humor in the Sasa advertisement “Persembahan Terbaik dari Sasa Omega 3.” This study is a descriptive qualitative research using the reception analysis method. The researcher categorized informants into three positions according to Stuart Hall: dominant hegemony, negotiation, and opposition. In-depth interviews were conducted with four informants, resulting in diverse findings influenced by differences in their backgrounds. The results showed that, regarding creativity, two informants held a dominant hegemonic position, one occupied a negotiation position, and the other held an opposition position. Regarding humor, three informants were in the dominant hegemonic position, while one was in a negotiation position.